2015
DOI: 10.1016/j.foodres.2015.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and flavor compound analysis of dealcoholized beer via one-step vacuum distillation

Abstract: The coupled operation of vacuum distillation process to produce alcohol free beer at laboratory scale and Aspen HYSYS simulation software was studied to define the chemical changes during the dealcoholization process in the aroma profiles of 2 different lager beers. At the lab-scale process, 2 different parameters were chosen to dealcoholize beer samples, 102 mbar at 50°C and 200 mbar at 67°C. Samples taken at different steps of the process were analyzed by HS-SPME-GC-MS focusing on the concentration of 7 flav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…At a laboratory for distillation processes, Andrés‐Iglesias et al. developed a dynamic Aspen HYSYS simulation for the prediction of the composition of alcohol‐free beers, which, however, does not permit transition to industrial scales. Corresponding simulations to predict the composition of alcohol‐free beers depending on the original alcoholic beers are increasingly of interest.…”
Section: Physical Methods For the Separation Of Ethanol From Fermentementioning
confidence: 99%
“…At a laboratory for distillation processes, Andrés‐Iglesias et al. developed a dynamic Aspen HYSYS simulation for the prediction of the composition of alcohol‐free beers, which, however, does not permit transition to industrial scales. Corresponding simulations to predict the composition of alcohol‐free beers depending on the original alcoholic beers are increasingly of interest.…”
Section: Physical Methods For the Separation Of Ethanol From Fermentementioning
confidence: 99%
“…The aroma, on the other hand, is linked to any volatile compound arising out of the beverage that can be perceived on the nose or retro-nasally, on the back of the mouth [43]. The main components associated with flavor are alcohols, phenols, esters, carbonyl compounds, and organic and fatty acids [52,53]. The marketing issues or labeling problems have been reviewed by Bellut and Arendt [29] and it was concluded that product labeling is a powerful tool for creating specific sensory expectations that can influence the consumer's choice.…”
Section: Non-alcoholic Beers: Alcohol-free and Low-alcohol Beersmentioning
confidence: 99%
“…In the batch process, the ethanol content was approximately twice that obtained by the continuous process. However, the concentration of esters in the study (26) was markedly lower. These factors changed the beer profile and quality, which demonstrated the benefit of adding standard beer or a fraction of the distillate from the top of the column to the bottom stream.…”
Section: Resultsmentioning
confidence: 58%
“…The beer produced via the batch vacuum distillation was compared to the final product of the simulated Processes B and C (Table ). In the batch process, the ethanol content was approximately twice that obtained by the continuous process.…”
Section: Resultsmentioning
confidence: 99%